REBEL CAUCASIAN REGIONS ON THE BRINK OF ENERGY WARS - MAGOMEDOV, Arbakhan; NIKEROV, Ruslan (CENTRAL ASIA AND THE CAUCASUS, 2010)
This article examines the problems associated with the struggle over Caspian energy resources (at different stages of the post-communist period) and the regional interests of the rebel Caucasian regions. We think that this approach might shed light on the reasons for the current conflict-prone nature of the region and help us to understand the true reason for the August 2008 war in South Ossetia and the motives of the sides participating in it.